2003
DOI: 10.1074/jbc.m212000200
|View full text |Cite
|
Sign up to set email alerts
|

Essential Role of the Unusual DNA-binding Motif of BAG-1 for Inhibition of the Glucocorticoid Receptor

Abstract: The co-chaperone BAG-1 is involved in the regulation of steroid hormone receptors, including the glucocorticoid receptor (GR). More recently, BAG-1 was found in the nucleus where it decreases GR transactivation. Moreover, nonspecific DNA binding of BAG-1 has been reported. We discovered that of the N-terminal part of BAG-1M, the first 8 amino acids are sufficient for DNA binding, containing a stretch of three lysines and a stretch of three arginines. Changing the spacing between these stretches had no effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
64
0
4

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 60 publications
0
64
0
4
Order By: Relevance
“…Previous studies have already demonstrated that Hsp70 selectively targets the TPR domains in SGT1 (41) and heat-shock organizing protein (Hop) (42), whereas CyP40 (43) and carboxy terminus of Hsc-70 interacting protein (CHIP) (44) are less discriminatory and can bind either Hsp90 or Hsc70. The outer mitochondrial membrane transporter Tom-70 is also a TPR protein able to provide a docking site for both chaperones, favoring the mitochondrial import of proteins (45,46). This makes Tom-70 a possible carrier for FKBP51.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have already demonstrated that Hsp70 selectively targets the TPR domains in SGT1 (41) and heat-shock organizing protein (Hop) (42), whereas CyP40 (43) and carboxy terminus of Hsc-70 interacting protein (CHIP) (44) are less discriminatory and can bind either Hsp90 or Hsc70. The outer mitochondrial membrane transporter Tom-70 is also a TPR protein able to provide a docking site for both chaperones, favoring the mitochondrial import of proteins (45,46). This makes Tom-70 a possible carrier for FKBP51.…”
Section: Discussionmentioning
confidence: 99%
“…Cell Culture, Transfection, and Assays for Luciferase and ␤-Galactosidase-Cultivation and transfection of human neuroblastoma SK-N-MC cells (American Type Culture Collection catalog number HTB-10), HeLa cells, HEK, and H4-II-E-C3 cells were as described previously (29,30). Two days before transfection, cells were seeded in medium containing charcoal-stripped serum.…”
Section: Methodsmentioning
confidence: 99%
“…Bag-1 proteins have been shown to act as cochaperones that modulate the activity of Hsc70/Hsp70 (Hohfeld and Jentsch, 1997;Takayama et al, 1997;Zeiner et al, 1997) and to bind and activate the serine/threonine kinase Raf-1 (Wang et al, 1996). Bag-1 proteins also bind to a variety of protein tyrosine kinase receptors (Bardelli et al, 1996) and nuclear hormone receptors (Zeiner and Gehring, 1995;Liu et al, 1998;Witcher et al, 2001;Schmidt et al, 2003). Bag-1 is expressed by a variety of cell types, including chondrocytes, during development and in adult tissues Crocoll et al, 2000).…”
mentioning
confidence: 99%